PENGARUH BUDAYA ORGANISASI TERHADAP KNOWLEDGE SHARING - Putri, Mariza Cindo; Raharso, Sri (POLITEKNIK NEGERI BANDUNG, 2016)
Business organizations must have good characteristics and a differentiator from other organizations. Business organizations that have a strong organizational culture will be able to last a long time and can deal with change. An organizational culture consists of norms and values that guide the behavior of members of the organization. The behavior of members of the organization that occurred in the workplace one of them is knowledge sharing activities. In a learning organization, to gain new knowledge sharing activity is needed. With a strong organizational culture, knowledge sharing activities can be run successfully. This study aims to investigate the influence of organizational culture on knowledge sharing in PT Sandy Globalindo. The method used in this research is descriptive and associative, while the data collection techniques are to do interviews and distributing questionnaires to 135 employees by the census. The results of the descriptive analysis stating the organization's culture and knowledge sharing in PT Sandy Globalindo classified in either class. Based on the research that has been done, regression equation of Y = 9.790 + 0,608X. The study states that there is a positive relationship between organizational culture and knowledge sharing in PT Sandy Globlindo at 0.608 and organizational culture affects knowledge sharing of 36.9%.